Long-term use of an ankle-foot orthosis intervention in patients with peripheral artery disease using the integrated promoting action on research implementation in health services (i-PARIHS) framework. (1st February 2023) - Bashir, Ayisha Z.; Dinkel, Danae M.; Pipinos, Iraklis I.; Estabrooks, Paul A.; Johanning, Jason M.; Myers, Sara A.
Abstract: Background: Peripheral artery disease (PAD) is a cardiovascular disease that limits patients' walking ability. Persistent ankle-foot orthosis (AFO) use may increase the distance patients can walk as well as physical activity. Purpose: The purpose of the study was to determine the implementation and patients' perspectives related to the use or disuse of the AFO intervention six months post-intervention. This study was guided by a semi-structured interview and survey based on the integrated Promoting Action on Research Implementation in Health Services (i-PARIHS) constructs. Design: A convergent mixed methods design was used to evaluate participants' perceptions six months following a three-month AFO intervention. A survey and semi-structured questionnaire based on the i-PARIHS constructs were administered and analyzed. Setting: Vascular surgery clinic and biomechanics research laboratory. Participants: Patients ( N = 7; male, 100%; age, 71.9 ± 0.6.7y; body mass index, 29.0 ± 0.5.5; ankle brachial index 0.50 ± 0.17) with claudication completed the study. Interventions: A certified orthotist fit participants with an AFO that was worn for 3 months. Main outcome measures: Qualitative analysis of semi-structured interviews and quantitative analysis of the survey. Results: The highest positive ratings were seen in the dimensions of usability and cost-effectiveness. The patients found the AFO device and instructions to wear, easy when starting the intervention and there were no out-of-pocket costs. The lower scores and challenges faced with observability and relative advantage domains indicated issues related to motivation for sustained use of the AFO. Conclusions: Barriers associated with AFO function that prevent common activities and poor health seem to be the biggest issue for not wanting to wear the AFO after the 3-month intervention. Addressing patients' perceptions and challenges to wearing the AFO is essential to increasing compliance and physical activity. Future research should concentrate on understanding the compatibility of orthotic device interventions with the subject's lifestyle. Clinical Trial Registration No.: NCT02902211. Highlights: Chronic peripheral artery disease causes muscle weakness that impairs walking. An ankle-foot orthosis may improve the distance patients with peripheral artery disease can walk. 6 months post-intervention questionnaire assessments were based on i-PARIHS framework.